Implementasi Teknologi Data Mining dan Notifikasi Bot untuk Mendukung Keputusan Trading Cryptocurrency - Rizky Parlika; Riky Hermawan; Rendra Ardika; Arif Nur Cahyo; Muhammad Wifaqul Azmi; Misbahul Munir (TeIKa, 2025)
Cryptocurrency trading has an extremely high level of price volatility, which creates the need for traders to have a decision support system capable of providing market analysis quickly and adaptively. Therefore, the automated system developed in this study integrates data mining technology and a Telegram bot to strengthen traders in making buy–sell decisions for crypto assets. This system uses the public API of Indodax to obtain real-time price data and analyzes it using the RSI indicator dynamically, rather than relying on static indicator data. The analysis results are then connected to a Telegram bot, enabling it to send automatic notifications when overbought or oversold conditions occur. In addition, these automated results are also utilized in a system that has already integrated previous RSI analysis. Through the “before, now, and after” perspective, the system is able to provide updated prices, the latest interactive charts, and reminders via the bot, making it easier for users to monitor the market and respond to opportunities. This approach offers an integrated solution for trading decision-making based on technical analysis and real-time communication, as it increases the speed of decision-making and demonstrates flexibility in analyzing various coin pairs and time frames.